Translation of Kompositum of German Legal Texts Into Indonesian: A Comparative Analysis Between Google Translate And DeepL - Uryadi, Uryadi; Agustin, Rina; Rachma, Azka Adilya (Universitas Negeri Makassar, 2025)
Abstract. This study examines the translation of kompositum (compound words) in German legal texts into Indonesian through a qualitative comparative analysis of two machine translation tools: Google Translate and DeepL. The analysis is conducted based on three key criteria: accuracy, acceptability, and readability. Selected legal texts containing complex kompositum, such as